DESIGN OF TEMPERATURE AND CURRENT MONITORING SYSTEM IN COLD STORAGE USING ARDUINO AT CV JALADRA TEKNIK COLD STORAGE BANTUL, YOGYAKARTA - Doly Andrian Harahap,; Hermawan, Ade; M. Yusuf Syam,; Hendro Sukismo,; Teguh Binardi,; Achmad Syarifudin,; Riko Satriyo Wibowo, (Journal of Innovation Research and Knowledge, 2024)
Monitoring is an activity carried out to find out the process of running a program that has been designed, whether it is running well as planned and find out the problems that occur. The monitoring system will facilitate a job if it is designed and carried out effectively. In this study the authors have an innovation to make a temperature control device to be added to the cold storage unit machine, so that it can be monitored using a smartphone or PC when the refrigeration system is operated. Temperature control is done by Arduino. Meanwhile, monitoring will be done using the Blynk application from a smartphone when setting the temperature or monitoring. It is expected that the addition of facilities in the cold storage unit can simplify the setpoint setting. In addition, the value of temperature monitoring can be done remotely. The research material used is cold storage and the equipment used is Nodemcu Esp8266 microcontroller, dht22 temperature sensor, acs712 electric current sensor, 20x4 i2c (inter integrated circuit) LCD, micro usb cable, jumper cable, Casing Box X6, and workshop equipment, and other supporting equipment. Sensor reading results are displayed using the Blynk application or website